EFEKTIVITAS KONTRAK BAKU DALAM MOBILITAS BISNIS: (Perspektif Hukum Progresif) - Adityo, Rayno Dwi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
The development of the world current business carrying logical konsuekwenses to make the birth of the new legal instrument that can respond the needs of business practition .Where instrumental law it can reflect a sense of justice but not forget the aspect of certainty in law. They called the instrument as a contract inside the agreement. But then became called as standard contract that has been determined by party its maker. Problems emerged at a later date related to what is called standard as contract, the practition of law may have different opinions, there is a negative views in also have positive views. This view born with regard to standard contract have a exemtion clause .Progressive law looked law as institutions which guarantee justice, make harmony between law and the human. It means that extent of standard contract was able to meet than legal purposes of the progressive and not opposed to fundamental norm in agreement and not opposed to regulations such as Undang-undang no 8 Tahun 1999 Tentang Perlindungan Konsumen, so the existence of legal contract until it .That contract default recognized or not they needed to answer time progress in current mobility business by efficiency time, cheaper charges but keep the justice and legal certainty.